Recent records of mealybugs and their parasitoids in Nelson pipfruit orchards. Issue 1 (2nd January 2017) - Shaw, P. W.; Charles, J. G.; Wallis, D. R.; Davis, V.
ABSTRACT: The majority (65%–94%) of mealybugs collected from harvested apples in Nelson, New Zealand, orchards between 2008 and 2011 were Pseudococcus longispinus . The remainder (35%–6%) were P. calceolariae, although a few P. viburni were occasionally found. Traps baited with newly developed synthetic pheromone of P. calceolariae were deployed in orchards in 2011 and attracted females of the mealybug parasitoid Alamella mira . The mealybug parasitoid complex in Nelson apple orchards was assessed over an 8-week period in autumn during 2012 and 2013 by deploying sentinel mealybugs on sprouting potatoes. Potatoes were infested with P. longispinus (in 2012 and 2013) and P . calceolariae (2012 only). They were deployed in orchards to capture parasitoids that were active during the trapping period. The sentinel mealybug-infested potatoes were placed in delta traps in the orchards for about 2 weeks and then retrieved and held in a laboratory in Auckland for 4–6 weeks. Parasitoid mummies were collected and emerging adults identified to species. In 2012, four species ( Tetracnemoidea peregrina, T. brevicornis, Coccophagus gurneyi and Ophelosia charlesi ) were recovered from three orchards near Motueka. In 2013, three species ( T. peregrina, C. gurneyi and Gyranusoidea advena ) were recovered. Monitoring methods appeared to influence the complex of parasitoids recovered. A combination of monitoring methods, including possible kairomonal responses of mealybug parasitoids to host pheromones and rearing parasitoids from fruit and foliage naturally infested with mealybugs, may provide the best assessment of mealybug parasitoid diversity and abundance in orchards.